Diagnostic efficacy of soluble ST2 in pediatric fulminant myocarditis - Huang, YanZhu; Lin, YiHu; Fu, MingHong; Zhang, WeiFeng (Frontiers in Pediatrics, 2025)
Background and aimsEarly identification of fulminant myocarditis (FM) is the key to reducing mortality, but there is still a lack of effective biomarkers for diagnosis. The aim of this study was to investigate the value of soluble ST2 (sST2) in identifying FM in children.MethodsThis was a single-center clinical observational study. We consecutively enrolled 144 children younger than 14 years of age diagnosed with viral myocarditis between January 2018 and November 2023, of whom 63 were diagnosed with FM.ResultsThe sST2 level in the FM group was significantly higher than that in the non-FM group [104.40 (68.80, 150.10) vs. 38.30 (19.85, 55.05), p < 0.001]. ROC curves showed that the optimal cut-off values of sST2, TNI, NT-proBNP and CRP for FM were 63.8 ng/ml, 13.3 ng/ml, 3182 pg/ml and 26.5 mg/L, respectively. The sensitivity and specificity of sST2 were 84.13% and 88.9%, indicating the highest early diagnosis efficiency. Multifactorial correction showed that sST2 ≥ 63.8 ng/ml and NT-proBNP ≥ 3182 pg/ml were independent diagnostic predictors of FM (OR = 22.374, 95% CI: 8.140 ∼ 61.499, P < 0.001), and (OR = 3.208, 95% CI: 1.163 ∼ 8.846, P = 0.024).ConclusionsWith high sensitivity and specificity, sST2 may serve as a strong predictor of pediatric FM.